The Rationality of Talāq in Islamic Family Law: Thoughts of Ibn Qayyim al-Jauziyyah - Burhanuddin (Syakhsiyah Jurnal Hukum Keluarga Islam, 2026)
This article examines the rationale of ta‘lik ṭalāq (conditional divorce) in Islamic family law through the jurisprudential paradigm of Ibn Qayyim al-Jauziyyah. While existing literature primarily focuses on the formal-textual validity of conditional divorce, a gap remains in applying classical teleological jurisprudence to reconcile the friction between static normative doctrines and extrajudicial practices in Indonesia. This qualitative study analyzes Ibn Qayyim’s foundational treatises using a normative-philosophical approach grounded in maqāṣid al-sharī‘ah. Findings reveal that Ibn Qayyim conceptualizes ta‘lik ṭalāq not as a formalistic procedure, but as a teleological mechanism contingent on intentionality, equity, and socio-legal utility (maṣlaḥah). Consequently, this research advances contemporary Islamic family law discourse by deconstructing rigid legalism and recontextualizing ta‘lik ṭalāq from a mere instrument of marital dissolution into a proactive mechanism for social justice. Furthermore, it provides a conceptual framework for state institutions to regulate conditional divorce, thereby protecting marginalized women and dependents in modern Muslim families.